IDEOLOGI PELESTARIAN LINGKUNGAN HIDUP DI BALIK PEMAKAIAN SAPUT POLENG PADA POHON BESAR DI BALI - Suda, I Ketut (Bumi Lestari; Vol 10 No 2 (2010), 2010)
This study concern to discuss about ideology wich talking about the used of ‘’saput poleng’’ in a big tree in Bali. Where for Hindus people means to remains the environment. But in fact that’s only just text, because some or maybe much environment be in big trauble. For example, ‘’Vila Bukit Berbunga’’ case in Tabanan and Buleleng region, the condition of critical area, in forest area is 3.538 ha very critical, 6.286 ha critikal, and 44.201 ha is alittle bit critical, and then all critical area is in 54.205 ha. Then the critical area far from forest area 84.885 ha. Based on Forest Departemen 2002, the damaged of forest in Bali is Caused by fired wich demage 544,19 ha; caused by people (illegal wood cutter) wich demage 83,17 m3/ph, and caused by ‘’pembibrikan’’ wich damage 5.245,77 ha. Beside that ‘’Galian C’’ erotion, tourism development (Bappeda Provinsi Bali, 2006: IX-14—IX-15). Is take a part to damage it. To prevent the damaged environment Balinesse has two way, there are ‘’sekala and niskala’’. Sekala way is make some low to protect forest area and niskala way is make some Hindus ritual.
Keywords: saput poleng, ideology, environment, a big tree